Experimental assessment of energy absorption capability and crushing behaviour of hybrid composite square tube subjected to oblique loadings - Lim, Keng Teek (2014)
Hybrid composite materials had been widely used as energy absorber devices during crushing or accident mainly in automobile as well as aircraft in this era. They had been effectively applied in the various industries for its light weight, high resistance to chemical and temperature and part integration purposes from military to public service levels. Previous studies have shown that axially crushing of tube yielded very good energy absorption capability. However, lack attentions have been given to the analysis of the oblique compressive tests of Kevlar/glass hybrid square tubes as well as pure Kevlar or fiberglass square tube. This research were focused on the 200g/m2 and 600g/m2 woven roving C-glass square tube, pure Kevlar-29 and hybrid of the 200g/m2 C-glass and Kevlar-29 square tubes subjected to quasi-static oblique loads. The main objective of the investigation was to study the effect of oblique loadings to the crushing behavior and energy absorption characteristics of the pure and hybrid square tubes. Comparison of the performance among the different materials on the crushing tubes were also been carried out. The crushing patterns of the tubes were investigated at loading angles of 0o , 5o , 10o , 15o and 20o with respect to the longitudinal direction of the tube. Square tubes were fabricated by using a square steel bar and by the mean of hand lay-up process. The oblique load was realized by applying a load via the inclined compression plate to the specimens. When the structures are subjected to the axial and oblique quasi-static loading, the deformation modes, such as progressive collapse, axisymmetric collapse, bending and buckling of the tubes were identified. Results showed that the energy absorption effectiveness factors of axial loading tube structures were significantly higher than those subjected to higher angles of oblique loadings. The hybrid composite Kevlar/Glass tube had the highest energy absorption capability compared to pure C-glass and pure Kevlar composite tubes.